Effect of Soluble CD4 on Exposure of Epitopes on Primary, Intact, Native Human Immunodeficiency Virus Type 1 Virions of Different Genetic Clades - Mbah, Henry A. (American Society for Microbiology (ASM), 2001)
We have used a virus-binding assay to examine conformational changes that occur when soluble CD4 (sCD4) binds to the surface of intact, native, primary human immunodeficiency virus type 1 virions. The isolates examined belong to seven genetic clades (A to H) and are representative of syncytium-inducing and non-syncytium-inducing phenotypes. Conformational changes in epitopes in the C2, V2, V3, C5, and CD4 binding domain (CD4bd) of gp120 and the cluster I and II regions of gp41 of these viruses were examined using human monoclonal antibodies that are directed at these regions. The studies revealed that sCD4 binding causes a marked increase in exposure of epitopes in the V3 loop, irrespective of the clade or the phenotype of the virus. Sporadic increases in exposure were observed in some epitopes in the V2 region, while no changes were observed in the C2, C5, or CD4bd of gp120 or the cluster I and II regions of gp41.